1999
DOI: 10.1016/s0933-3657(99)00014-7
|View full text |Cite
|
Sign up to set email alerts
|

Refining instructional text generation after evaluation

Abstract: In this paper, we describe how user-adapted explanations about drug prescriptions can be generated from already existing data sources. We start by illustrating the two-step approach employed in the first version of the natural language generator and the limitations of generated texts, that we discovered through analytical and empirical evaluations. We claim that, although style refinement would be needed in these texts, particular care should be devoted to implementing some of the persuasion techniques that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…This paper described two of these text modification problems, and introduced two algorithms to solve them. The algorithms' results have been evaluated, and they were applied to two typical cases: re-structuring of one-shot documents [1] and generation of dynamic hypermedia. The two applications showed that these algorithms can be successfully used in practical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This paper described two of these text modification problems, and introduced two algorithms to solve them. The algorithms' results have been evaluated, and they were applied to two typical cases: re-structuring of one-shot documents [1] and generation of dynamic hypermedia. The two applications showed that these algorithms can be successfully used in practical contexts.…”
Section: Discussionmentioning
confidence: 99%
“…* The observation that conveying appropriate information to patients reduces the overall cost of health care has created a demand for health documents tailored to patients' needs and abilities. Several researchers developed systems that generate medical advice (Carenini et al, 1994;Binsted et al, 1995;Hirst et al, 1997;de Rosis et al, 1999). ** Carenini et al (1994) developed a system that advised patients about migraines and their treatment.…”
Section: Considering a User's Attributes^one-dimensional User Modelsmentioning
confidence: 99%
“…Two systems that generate health advice also consulted multi-dimensional user models (Hirst et al, 1997;de Rosis et al, 1999). Hirst et al (1997) developed an authoring tool for use by technical writers, which produced a £uent rendering of the information selected by these writers.…”
Section: Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the 'affective' aspects of communication are expressed in more or less overt form (Hovy, 1988;Walker et al, 1997;de Rosis et al, 1999;de Rosis and Grasso, 2000). We include in affective aspects of communication not only 'basic' emotions and mood, but also those aspects of the mind that are often considered as 'extrarational' in the artificial intelligence community: for instance, 'doubt' 'cognitive overload' and 'deception' (Carberry and Schroeder, 2001;Berthold and Jameson, 1999) .…”
Section: Introductionmentioning
confidence: 99%